Changing conceptions of death as a function of depression status, suicidal ideation, and media exposure in early childhood - Hennefield, Laura (J Am Acad Child Adolesc Psychiatry, 2019)
OBJECTIVE: This study characterized 3- to 6-year-old children’s understanding of death as a function of depression status, suicidal ideation (SI), and media consumption. METHOD: Participants were 79 depressed children (aged 3.0–6.11), who completed a comprehensive psychiatric assessment and experimenter-led death interview, and a comparison group of 60 healthy children (aged 4.0–7.12). The interview assessed children’s understanding of five concepts of death: universality, applicability, irreversibility, cessation, and causality. Children’s mastery of each concept, and overall death understanding, was examined as a function of depression and SI-status: depressed with SI (N=22), depressed without SI (N=57), and healthy (N=60). Children’s observed emotional reactions to hearing about natural death, accidental death, and suicide were assessed via death-themed stories. Parent-reports of children’s television and videogames/internet consumption assessed links between media exposure and death understanding. RESULTS: Depressed children with SI scored higher on overall death understanding than depressed without SI and healthy children. They also exhibited more sad and anxious affect listening to death-themed stories and were more likely to describe death as caused by violence. Across our sample, older children were also more likely to depict death as violent. More television use was associated with less understanding of death, including the concept of irreversibility. CONCLUSIONS: Depressed children with SI have a more advanced understanding of death than their peers dispelling the myth that these ideations arise in the context of poor death understanding. The increase in violence attributions across early childhood may indicate increasing normalization of violence in children’s perceptions of death. A Randomized Controlled Trial of PCIT-ED For Preschool Depression; http://clinicaltrials.gov; NCT00595283